Produção de ácidos graxos voláteis por fermentação anaeróbia de manipueira e de permeado de soro de queijo - Zempulski, Denise Aparecida (2013)
Cassava is a crop widely throughout the national territory. In 2011, the national production of cassava was estimated at 27.1 million tons, achieving an increase of 9.2% compared to the 2010 harvest. Among the liquid waste processing cassava, cites the Manipueira, it is the water content of the root mass extracted in pressing grated, in making flour. Manipueira residue is more problematic, because it has high pollution load and toxic potential due to the presence of cyanogenic glycosides, may cause serious problems to the environment and aquatic life if released into waterways. Other big environmental waste when discarded improperly, are waste dairy industries. The fractionation of milk constituents by ultrafiltration results in derivatives with great nutritional value and commercial, such as the retentate (concentrate fraction composed of protein and fat) and permeates (fraction diluted comprising lactose, minerals, electrolytes, nitrogen and water). Recently there is a higher quest for use of agro-industrial waste in order to recover substances and/or materials and thus increase economic efficiency of production processes. The application of agro-industrial residues in bioprocesses is used like alternative substrate, and a help to solve the problem of pollution in the processes of industrialization, where anaerobic digestion stands out due to its many favorable characteristics. One way to minimize environmental impacts and add value to the effluent is its use in the production of volatile fatty acids (VFA) production via anaerobic fermentation, which is the main objective of this work. All fermentations were performed at 30 ° C and 80 rpm with pig inoculum. Initially made up four fermentations, changing the substrate used (cassava, starchy hydrolyzate, whey permeate and synthetic medium) where obtained better results of VFA concentrations with cheese whey permeated and Manipueira. So, with these two substrates, was done the test without light (dark fermentation), and this new detail was responsible to increase the production of VFA in 38% for the manipueira and 20% for the permeate. Following an experimental design 22 was carried out with in quadruplicate central point for Manipueira, where they were tested three levels of glucose concentration (9, 19 e 29 g.L-1) and sodium bicarbonate (0.21, 1.71 and 3.21 g.L-1), and glucose concentrations of 29 g.L-1 and bicarbonate 3.21 g.L-1 that resulted in the increased production of VFA (1941,4 mg L-1 in 23 h) representing an increase of 77,3% in production. For the cheese whey permeate also was done test changing the glucose (75, 45 e 25 g.L-1) and alkalinity (7,7, 8,14, 9,2, 10,26 e 10,7 g.L-1). The best levels founded in this work for the permeate are 45 g.L-1 of glucose and 10,26 g.L-1 of alkalinity, resulting in 4115,16 mg.L-1 of VFA in 41 h.